2D Nitrogen‐Containing Carbon Material C5N as Potential Host Material for Lithium Polysulfides: A First‐Principles Study. Issue 2 (30th November 2018) - Wang, Dandan; Li, Haibo; Zhang, Liangliang; Sun, Zhonghui; Han, DongXue; Niu, Li; Zhao, Jialong
Abstract: Two‐dimensional (2D) materials are identified to be efficient in many applications. In this work, a novel 2D nitrogen‐containing carbon material, C5 N, is theoretically designed through structure changes in atomic scale, that is, introducing VC –VN bivacancy defects along lines in perfect C3 N monolayer. C5 N monolayer is verified to be chemically, mechanically, dynamically, and thermodynamically stable based on cohesive energy, elastic constants, phonon spectrum, and molecular dynamics calculations. C5 N is determined to be metallic which is an important property for battery electrode. Moreover, the anchoring performance of S8 and Li2 S n ( n = 1, 2, 4, 6, and 8) on C5 N monolayer and the anchoring mechanisms are explored. The adsorption energies are calculated to be −0.24, −1.20, −1.10, −1.06, −1.63, and −1.59 eV for S8, Li2 S8, Li2 S6, Li2 S4, Li2 S2, and Li2 S, respectively. The anchoring effect of Li2 S n on C5 N monolayer originates from the charge transfer between lithium polysulfides and C5 N surface. These results reveal that C5 N monolayer is a promising host material for polysulfides in Li–S batteries. Our calculations illustrate the design of nanostructures and facilitate the application of carbon‐based 2D materials in environment and energy. Abstract : A novel 2D nitrogen‐containing carbon material C5 N is designed through introducing VC –VN bivacancy defects along specific lines in perfect C3 N monolayer, based on first‐principles calculations. The C5 N monolayer is composed of "5 carbon nitrogen ring‐8 carbon nitrogen ring‐5 carbon ring." C5 N is demonstrated to possess metallic characteristic and expected to be a promising host material for polysulfides.